2004
DOI: 10.1139/v04-024
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting lipid – general anesthetic interactions (II): Halothane location and changes in lipid bilayer microenvironment monitored by fluorescence

Abstract: A universal mechanism for the action of general anesthetics (GA) is not yet available. In this study, we investigated the interaction between halothane and 1,2-dipalmitoyl-sn-3-glycero-3-phosphocholine (DPPC) and 1,2-dioleoyl-sn-3-glycero-3-phosphocholine (DOPC) bilayers labeled with Laurdan, Prodan, and NBD-C6-PC as the reporter probes using steady-state fluorescence spectroscopy. We have evidence that halothane is located on the acyl chain side, near the headgroup region of the bilayer. Additionally, we find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 31 publications
1
20
0
1
Order By: Relevance
“…Although the molecular mechanisms of local anaesthetics action are still not completely understood, three main hypotheses are generally considered to explain them: direct interaction with voltage-gated sodium channels, induction of structural alterations in the lipid matrix of the biomembranes and action on the lipid-protein interfaces [1,2]. In the latter two cases, the mechanisms involve nonspecific interactions of the anaesthetics with the lipid bilayers.…”
Section: Introductionmentioning
confidence: 99%
“…Although the molecular mechanisms of local anaesthetics action are still not completely understood, three main hypotheses are generally considered to explain them: direct interaction with voltage-gated sodium channels, induction of structural alterations in the lipid matrix of the biomembranes and action on the lipid-protein interfaces [1,2]. In the latter two cases, the mechanisms involve nonspecific interactions of the anaesthetics with the lipid bilayers.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, we examined the location of inhaled anesthetic in a fluorescently labeled DOPC lipid bilayer (25). We found that halothane locates on the acyl chain side, near the headgroup region of the bilayer (25). Therefore, we might anticipate a heterogeneous distribution of halothane around gramicidin in bilayer environments.…”
Section: Resultsmentioning
confidence: 99%
“…This was done to ascertain the effect of the local environment on halothane-gramicidin interactions. In previous work, we examined the location of inhaled anesthetic in a fluorescently labeled DOPC lipid bilayer (25). We found that halothane locates on the acyl chain side, near the headgroup region of the bilayer (25).…”
Section: Resultsmentioning
confidence: 99%
“…The second, short-range regime, between 0.3 and 4 nm, is attributed to the deformation of the bilayer. Most studies on the bilayer report a jump corresponding to the piercing of the bilayer for forces ranging from approximately 3 to 25 nN [71][72][73]. This jump into contact is observed when the force gradient exceeds the spring constant of the cantilever k, which is the case when k < 1 N/m.…”
Section: Repulsive Forcesmentioning
confidence: 99%